Kajian Pengembangan Sistem Nanostructured Lipid Carrier (NLC) Untuk Penghantaran Agen Inhibitor Tirosinase - Anindi Febrilia; Sani Ega Priani; Hanifa Rahma (UNISBA Press, 2022)
Abstract. Tyrosinase inhibitors is compounds that have anti-hyperpigmentation activity so it can be used for topical treatment. Stratum corneum as a skin protector from external stimuli makes it difficult for active substances to penetrate. Therefore, the development of preparation with Nanostructured Lipid Carrier (NLC) system was carried out to increase penetration and effectiveness of tyrosinase inhibitor agents to reach melanocyte cells. This study tries to investigate the formulation of NLC preparations contain tyrosinase inhibitor agents, as well as the effect of developing an NLC system on percutaneous penetration and therapeutic effectiveness of tyrosinase inhibitor agents. The study was conducted based on a Systematic Literature Review on articles from reputable databases that matched the inclusion and exclusion criteria. The results of study show that tyrosinase inhibitors have been developed into NLC preparations including kojic acid, deoxyarbutin, Ficus deltoidea extract, glabridin, hydroquinone, MHY908, piceatannol, and trans-resveratrol. The formulation of NLC preparations use solid lipids, liquid lipids and the addition of surfactants. The development of NLC system able to increase penetration of tyrosinase inhibitor agents it can see from increase the flux value or percent penetrated by 11.53-309.10%. The development of NLC system can increase effectiveness of tyrosinase inhibitor agents as anti-hyperpigmentation which is characterized by increase the L value, increase the % reduction in melanin, decrease the IC50 value, and increase the % tyrosinase inhibitory activity compared to the pure active substance or conventional preparations. Abstrak. Inhibitor tirosinase merupakan senyawa yang memiliki aktivitas sebagai anti hiperpigmentasi dapat digunakan untuk pengobatan topikal. Stratum korneum sebagai pelindung kulit dari rangsangan luar menyebabkan zat aktif sulit terpenetrasi. Maka dari itu dilakukan pengembangan sediaan dengan sistem Nanostructured Lipid Carrier (NLC) untuk meningkatkan penetrasi dan efektivitas dari agen inhibitor tirosinase untuk mencapai sel melanosit. Penelitian ini bertujuan untuk mengkaji formulasi sediaan NLC mengandung agen inhibitor tirosinase, serta pengaruh pengembangan sistem NLC terhadap penetrasi perkutan dan efektivitas terapi dari agen inhibitor tirosinase. Kajian dilakukan berbasis Systematic Literature Review terhadap artikel dari database bereputasi yang memenuhi kriteria inklusi dan eksklusi. Hasil kajian menunjukkan agen inhibitor tirosinase telah banyak dikembangkan menjadi sediaan NLC diantaranya asam kojat, deoxyarbutin, ekstrak Ficus deltoidea, glabridin, hidrokuinon, MHY908, piceatannol, dan trans-resveratrol. Formulasi sediaan NLC menggunakan lipid padat, lipid cair serta penambahan surfaktan. Pengembangan sistem NLC mampu meningkatkan penetrasi agen inhibitor tirosinase dilihat dari peningkatan nilai fluks atau persen terpenetrasi sebesar 11,53-309,10%. Pengembangan sistem NLC dapat meningkatkan efektivitas agen inhibitor tirosinase sebagai anti hiperpigmentasi ditandai dengan peningkatan nilai L, peningkatan % pegurangan melanin, penurunan nilai IC50, dan peningkatan % aktivitas penghambatan tirosinase dibandingkan zat aktif murni atau sediaan konvensional.